An Analysis of Positive and Negative Politeness Strategy in Ome TV by Fiki Naki on Youtube - Yanti Kristina Sinaga; Bloner Sinurat; Doris Yolanda Saragih; Nanda Saputra (LingLit Journal Scientific Journal for Linguistics and Literature, 2022)
The aims of this study were to identify the types of positive and negative politeness strategies and to find out the most dominant type of positive and negative politeness strategies found in Ome TV by Fiki naki on Youtube. The theory of politeness strategies was by Brown and Levinson (1987). The research method was descriptive qualitative research with content analysis, because the data were collected from document. The researchers chose 4 videos and title first “cewek paling cute and sweet” in Ome TV launched in February 5th, 2021 with a duration of 17 minutes, second “Fiki naki seneng banget ketemu calon istri baru cantik” launched in October 4th, 2021 with a duration of 13 minutes 19 second, third “ Ciwi ciwi Norwegia histeris karna ini”, launched in April 19th 2021 with duration 19 minutes 33 second , fourth “Aku Buat Heboh Cewe - Cewe Di Ome TV” launched in April 14th 2021 with duration 18 minutes 33 second. There were some steps in collecting the data, such as: familiarizing and organizing, coding and reducing, interpreting and representing. The result showed that there were 38 Positive and Negative politeness strategies found in Ome TV by Fiki naki on Youtube, they were: positive politeness 30 (79%), negative politeness 8(21%) . The most dominant type of politeness strategies found in Talk Show by Jimmy Fallon was Positive Politeness. Positive Politeness was done by speaker and hearer to made enjoyable situation, build good relation, good interaction. In conclusion, with this research we must be careful when used a language to communicate with other so that the conversation become run well.